Implantable piezoelectric / conductive double-layer composite membrane, stent, preparation method and application thereof

The problem of insufficient conductivity and mechanical strength in autologous nerve transplantation therapy is solved by using a double-layer composite membrane and scaffold of reduced graphene oxide and polylactic acid piezoelectric fibers in nerve transplantation. More effective peripheral nerve regeneration and damage repair are achieved.

CN119280484APending Publication Date: 2025-01-10NANTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411416987.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing autologous nerve transplantation therapy limits the effective repair of peripheral nerve damage due to the limited source of nerves available for transplantation, difficulty in matching the tissue structure and size, long-term deneurination in the transplant donor area, and differences in transplant efficacy.

Method used

Develop an implantable piezoelectric/conductive double-layer composite film and scaffold, a composite conductive biomaterial layer composed of reduced graphene oxide grafted by chitosan and chitosan and piezoelectric layer of polylactic acid piezoelectric fibers Combined, it provides mechanical structural support, conductivity and electrical signal output, and promotes peripheral nerve regeneration.

Benefits of technology

The double-layer composite film and scaffold have uniform conductivity, excellent mechanical strength and biocompatibility, which can maximize the transmission of electrical signals, promote nerve regeneration, provide better mechanical support and electrical signal output, and are suitable for different types of Repair of peripheral nerve damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119280484A_ABST
    Figure CN119280484A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides an implantable piezoelectric / conductive double-layer composite membrane, a stent, a preparation method and application thereof, and belongs to the field of tissue engineering and biological materials. The implantable piezoelectric / conductive double-layer composite film is composed of a composite conductive biological material layer and a piezoelectric layer, the piezoelectric layer is attached to and covers the composite conductive biological material layer, the composite conductive biological material layer is composed of chitosan and chitosan grafted reduced graphene oxide, and the piezoelectric layer is composed of piezoelectric fibers. The piezoelectric / conductive double-layer composite film provided by the invention not only provides enough mechanical structure support, but also provides good conductivity and electric signal output capability, has remarkable antibacterial performance, and has a better promotion effect on regeneration and repair of peripheral nerves.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of tissue engineering and biomaterials, and specifically relates to an implantable piezoelectric / conductive double-layer composite film and bracket, a preparation method and applications thereof. Background Art

[0002] Peripheral nerve injury is a very common clinical disease, mainly due to traction injury, cutting injury, firearm injury, compression injury, ischemia and other reasons leading to short-term or lifelong nerve dysfunction. It is estimated that there are millions of patients with peripheral nerve injury every year worldwide. Since the nerve itself has a weak ability to regenerate, it needs external treatment.

[0003] So far, autologous nerve transplantation has the most definite efficacy and is also the "gold standard" for evaluating the effectiveness of various nerve grafts. However, due to the limited sources of nerves available for transplantation, the difficulty in matching tissue structure and size, long-term denervation of the transplant donor area, and differences in transplantation efficacy, the widespread development of autologous nerve transplantation is limited. Therefore, the development of more effective peripheral nerve defect repair strategies is an urgent clinical need.

[0004] Tissue engineering neural scaffolds have attracted widespread attention due to their potential to replace autologous nerves. Chitosan (CS), a natural polymer obtained by deacetylation of chitin, is widely used in the preparation of tissue engineering scaffolds due to its advantages such as biocompatibility, non-toxicity, hydrophilicity, fast kinetics and high processability. Nerve grafts prepared using chitosan have been shown to have excellent ability to promote nerve regeneration. However, due to the lack of a conductive medium, a single chitosan neural conduit cannot establish a complete electrical signal transmission pathway when a nerve is defective, so it is necessary to add electroactive materials to it to assist cells in transmitting electrical signals.

[0005] Electroactive materials can be divided into two categories: conductive materials and piezoelectric materials, both of which essentially work by changing the bioelectric field of cells. Studies have found that the incorporation of electroactive substances into nerve repair grafts can promote the repair of damaged nerves by mediating cell adhesion, growth, migration, differentiation, DNA synthesis, protein secretion, and the release of related nutritional factors. Among them, reduced graphene oxide (rGO), as an electroactive inorganic material, has great potential in the field of peripheral nerve regeneration due to its excellent conductivity and unique biological properties. Compared with graphene, rGO has oxygen-containing functional groups, which increases its biocompatibility and safety. Compared with graphene oxide (GO), another important derivative of graphene, it has a stronger conductivity due to the sharp reduction of oxygen-containing functional groups.

[0006] Piezoelectric materials are non-conductive smart materials that mainly use the piezoelectric properties of the material itself to achieve self-generating performance. Because the crystal symmetry of piezoelectric materials is low, when deformed by external force, the positive and negative ions in the crystal will undergo relative displacement, causing the positive and negative charge centers to not coincide, resulting in macroscopic polarization of the crystal, which in turn generates charges, and the generated charges are located on the surface of the material. Piezoelectric materials can be divided into three categories: piezoelectric crystals, piezoelectric ceramics, and piezoelectric polymers. Compared with piezoelectric ceramics, piezoelectric polymers have good biocompatibility and piezoelectric properties, such as polylactic acid (PLLA). It can be prepared into nanofibers by electrospinning, thereby simulating the structure of the extracellular matrix (ECM) and promoting cell growth. In addition, by regulating the physical parameters of the nanofiber scaffold, such as porosity, elastic modulus, fiber diameter, hydrophilicity, and orientation, specific tissue application requirements can be met. Summary of the invention

[0007] The purpose of the present invention is to at least partially solve the above-mentioned technical problems, and aims to provide an implantable piezoelectric / conductive double-layer composite film and bracket with both piezoelectricity and conductivity, a preparation method and its application. In addition to providing sufficient mechanical structure support, the double-layer composite film also provides good conductivity and electrical signal output capability, has significant antibacterial properties, and has a better promoting effect on peripheral nerve regeneration and repair.

[0008] The technical solution provided by the present invention is as follows:

[0009] In a first aspect of the present invention, an implantable piezoelectric / conductive double-layer composite film is provided.

[0010] The implantable piezoelectric / conductive double-layer composite film is composed of a composite conductive biomaterial layer and a piezoelectric layer, wherein the piezoelectric layer is laminated and covered on the composite conductive biomaterial layer, the composite conductive biomaterial layer is composed of chitosan and chitosan-grafted reduced graphene oxide, and the piezoelectric layer is composed of piezoelectric fibers.

[0011] In some embodiments of the present invention, the composite conductive biomaterial layer includes a chitosan layer as a main supporting structure, and the chitosan-grafted reduced graphene oxide is continuously dispersed in the chitosan layer.

[0012] In some embodiments of the present invention, the piezoelectric fibers include polylactic acid as a main component.

[0013] In some embodiments of the present invention, the piezoelectric fiber comprises poly-L-lactic acid or poly-D-lactic acid as a main component.

[0014] In a second aspect of the present invention, a method for preparing an implantable piezoelectric / conductive double-layer composite film is provided. The implantable piezoelectric / conductive double-layer composite film is the above-mentioned implantable piezoelectric / conductive double-layer composite film. The preparation method comprises:

[0015] S1 prepares chitosan-grafted reduced graphene oxide powder;

[0016] S2 preparing a mixed solution containing a chitosan solution and the chitosan-grafted reduced graphene oxide;

[0017] S3: applying the mixed solution onto a support member and air-drying the mixed solution, and then washing and drying the mixed solution to obtain a composite conductive biomaterial layer;

[0018] S4: spinning a piezoelectric layer composed of piezoelectric fibers on the composite conductive biomaterial layer to obtain a piezoelectric / conductive double-layer composite film.

[0019] In some embodiments of the present invention, step S1 includes:

[0020] A mixed solution containing chitosan and graphene oxide is prepared, a reduction reaction is carried out at 80-100° C., a precipitate is obtained by centrifugation, and the precipitate is washed and freeze-dried to obtain powdered chitosan-grafted reduced graphene oxide.

[0021] In some embodiments of the present invention, in the mixed solution containing chitosan and graphene oxide, the mass ratio of chitosan to graphene oxide is (5-10):1.

[0022] In some embodiments of the present invention, the mixed solution containing chitosan and graphene oxide is prepared by the following method:

[0023] Dissolving chitosan powder in, for example, an acetic acid solution, stirring and standing at room temperature for 2 to 3 hours, removing residual bubbles, and obtaining a first chitosan solution, wherein the molecular weight of the chitosan is 200 to 300 KDa;

[0024] placing graphene oxide powder in deionized water and ultrasonically obtaining a graphene oxide dispersion;

[0025] The graphene oxide dispersion is added dropwise to the first chitosan solution, stirred at room temperature and ultrasonicated to obtain a mixed solution containing chitosan and graphene oxide.

[0026] In some embodiments of the present invention, in the mixed solution containing chitosan and the chitosan-grafted reduced graphene oxide, in the mixed solution containing chitosan and the chitosan-grafted reduced graphene oxide, the mass of chitosan is greater than the mass of the chitosan-grafted reduced graphene oxide.

[0027] In some embodiments of the present invention, in the mixed solution containing chitosan and the chitosan-grafted reduced graphene oxide, the mass ratio of chitosan to the chitosan-grafted reduced graphene oxide is (2-3):(1-2).

[0028] In some embodiments of the present invention, in the mixed solution containing chitosan and the chitosan-grafted reduced graphene oxide, the dosage ratio of chitosan, the chitosan-grafted reduced graphene oxide, acetic acid and deionized water is (0.4-0.6) g: (0.2-0.4) g: 0.4 g: 18.8 ml.

[0029] In some embodiments of the present invention, step S2 includes:

[0030] A second chitosan solution is prepared, and powdered chitosan-grafted reduced graphene oxide is added to the second chitosan solution, and stirred evenly to obtain a mixed solution containing the chitosan solution and the chitosan-grafted reduced graphene oxide.

[0031] In some embodiments of the present invention, step S3 includes:

[0032] The mixed solution containing the chitosan solution and the chitosan-grafted reduced graphene oxide is (evenly) wet coated on an adhesive glass slide, and then placed on a horizontal surface to stand until bubbles are completely removed, and then kept horizontally for ventilation and air drying to obtain a film-like composite conductive biomaterial layer.

[0033] In some embodiments of the present invention, after ventilation and air-drying in step S3, the sample is washed with NaOH and deionized water in sequence and air-dried.

[0034] In some embodiments of the present invention, step S4 includes:

[0035] Dissolving poly-L-lactic acid in a solvent and stirring to obtain a spinning solution;

[0036] The spinning solution is spun in the form of fibers on the composite conductive biomaterial layer by electrostatic spinning to form a piezoelectric layer composed of piezoelectric fibers.

[0037] In some embodiments of the present invention, in step S4,

[0038] The solvent is obtained by mixing dichloromethane and N,N-dimethylformamide. The two reagents are selected for mixing, and only dichloromethane is used in a single ratio. The mixing can improve the crystallinity of PLLA, which is a factor that affects the piezoelectric performance.

[0039] In some embodiments of the present invention, the mass ratio of poly-L-lactic acid, dichloromethane and N,N-dimethylformamide in the spinning solution is 0.25:2.85:1.9. This solvent and solute parameter is the best in the electrospinning process and will not produce adhesion.

[0040] In some embodiments of the present invention, in step S4,

[0041] The specific process of electrospinning is: fix the composite conductive biomaterial layer on the drum collector, transfer the spinning solution to the syringe equipped with the electrospinning machine, set the spinning parameters, and spin the spinning solution in the form of fibers on the composite conductive biomaterial layer.

[0042] In a third aspect of the present invention, an implantable piezoelectric / conductive double-layer composite stent is provided. The implantable piezoelectric / conductive double-layer composite stent is made of the implantable piezoelectric / conductive double-layer composite film described above or prepared by the above preparation method.

[0043] In a fourth aspect of the present invention, a method for preparing an implantable piezoelectric / conductive double-layer composite stent is provided, the preparation method comprising the following steps:

[0044] Winding the implantable piezoelectric / conductive double-layer composite film as described above or prepared by the preparation method as described above on a support rod;

[0045] Coating the side joints with methacrylated gelatin;

[0046] The methacryloyl gelatin is solidified by ultraviolet irradiation to form a double-layer composite stent with a through lumen;

[0047] The outer layer of the double-layer composite stent is a piezoelectric layer, and the inner layer is a composite conductive biomaterial layer.

[0048] In some embodiments of the present invention, the support rod comprises a stainless steel round bar;

[0049] The amino substitution degree of the methacryloyl gelatin is 30-90±5%, the molecular weight is 100-200KDa, and the concentration is 5-10%.

[0050] In the fifth aspect of the present invention, there is provided an implantable piezoelectric / conductive double-layer composite film as described or prepared by the described preparation method, an implantable piezoelectric / conductive double-layer composite stent as described, and the use of the piezoelectric / conductive double-layer composite stent prepared by the described preparation method in the preparation of an implantable piezoelectric / conductive double-layer composite stent for repairing nerve damage.

[0051] The implantable piezoelectric / conductive double-layer composite film and stent, preparation method and application thereof according to the embodiments of the present invention have at least one of the following advantages or at least a part of at least one of the advantages:

[0052] (1) In the embodiment of the present invention, chitosan-grafted graphene oxide is subjected to reduction reaction to prepare chitosan-grafted reduced graphene oxide, and chitosan is then used to disperse the chitosan-grafted reduced graphene oxide, so that the reduced graphene oxide can be evenly dispersed in the reaction system. In the prepared composite conductive biomaterial layer, the reduced graphene oxide is evenly distributed in the chitosan layer. On the one hand, the obtained conductive film has uniform conductivity (rGO can form a continuous path for conduction) and excellent mechanical strength. At the same time, chitosan imparts excellent biocompatibility and can avoid cytotoxicity caused by excessive reduced graphene oxide. On the other hand, the reduced graphene oxide evenly distributed in the chitosan layer forms a rough surface of the composite conductive biomaterial layer, which is conducive to the close combination of the piezoelectric fibers formed by electrospinning and the composite conductive biomaterial layer, forming a double-layer membrane structure with an outer layer of PLLA piezoelectric layer and an inner layer of a conductive layer composed of chitosan and chitosan-grafted reduced graphene oxide. The charge generated by the piezoelectric layer is located on the surface of the piezoelectric layer, and then transmitted outward through the connected and fitted conductive layer, which can maximize the transmission of electrical signals, thereby better inducing the growth of the two broken end nerves toward the middle, and preventing the downstream target muscles / organs from atrophying due to long-term loss of electrical stimulation;

[0053] (2) The natural polymer chitosan serves as the main support structure of the stent, providing good mechanical support for the entire catheter. The chitosan-grafted reduced graphene oxide continuously dispersed in the chitosan layer acts as a conductive medium. Poly-L-lactic acid serves as a piezoelectric layer, providing electrical signal output for the entire composite stent, which together give the catheter piezoelectric and conductive properties.

[0054] (3) Graphene oxide is grafted with chitosan through an amide reaction, and the graphene oxide is reduced to reduced graphene oxide, thereby further improving the dispersibility, conductivity and biocompatibility of the reduced graphene oxide in the chitosan solution;

[0055] (4) The present invention directly covers the poly-L-lactic acid fiber layer produced by electrospinning on the conductive layer, which can transmit the generated electrical signal to the conductive layer to the greatest extent; at the same time, the piezoelectric / conductive double-layer composite stent is an implantable stent, and its piezoelectric layer in the body can directly receive muscle pressure stimulation, thereby quickly and effectively generating an electrical signal response;

[0056] (5) The substrates selected in the present invention are all green and harmless materials that are biodegradable and biocompatible. They are completed in a neutral environment through acid-base neutralization, which simplifies the production process and greatly avoids the adverse effects caused by toxic organic solvents remaining in in vitro cell culture and scaffold implantation in vivo;

[0057] (6) The implantable piezoelectric / conductive double-layer composite stent of the present invention has better mechanical support, better conductivity, better electrical signal output capability, better antibacterial effect, provides a favorable microenvironment for cell adhesion, proliferation and differentiation, has a better promoting effect on peripheral nerve regeneration and repair, and can be more widely applicable to different types of peripheral nerve injury repair;

[0058] (7) The piezoelectric layer is covered on the surface of the conductive layer by electrospinning, and then curled into a double-layer piezoelectric / conductive stent with a through-hole in the middle. The formed stent has good conductivity, electrical signal output performance, mechanical properties and biosafety, and can provide good physical support and regenerative microenvironment for the repair of peripheral nerve injury. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] These and / or other aspects and advantages of the present invention will become apparent and readily understood from the following description of the preferred embodiments in conjunction with the accompanying drawings, in which:

[0060] Figure 1 a to Figure 1 f is a schematic diagram of SEM characteristics of the implantable piezoelectric / conductive double-layer composite stent according to Examples 1-5 of the present invention;

[0061] Figure 2 Statistical graphs of Young's modulus of the implantable piezoelectric / conductive double-layer composite stents according to Examples 1-5 of the present invention and the stent of Comparative Example 1;

[0062] Figure 3 It is a statistical graph of the electrical conductivity of the implantable piezoelectric / conductive double-layer composite stent according to Examples 1-5 of the present invention and the stent of Comparative Example 1;

[0063] Figure 4 a to Figure 4 d is an electrical signal output diagram of the implantable piezoelectric / conductive double-layer composite stent described in Example 2 of Test Example 1 according to the present invention and the stent of Comparative Example 1;

[0064] Figure 5 It is a statistical graph of membrane blood compatibility of the implantable piezoelectric / conductive double-layer composite stent described in Examples 1-4 in Test Example 2 of the present invention and the stent of Comparative Example 1;

[0065] Figure 6It is a statistical graph of the MTT method cytotoxicity verification of the implantable piezoelectric / conductive double-layer composite stent described in Examples 1-4 in Test Example 3 of the present invention and the stent of Comparative Example 1. DETAILED DESCRIPTION

[0066] The technical solution of the present invention is further specifically described below by examples and in conjunction with the accompanying drawings. In the specification, the same or similar reference numerals indicate the same or similar components. The following description of the embodiments of the present invention with reference to the accompanying drawings is intended to explain the overall inventive concept of the present invention and should not be construed as a limitation of the present invention.

[0067] According to an embodiment of the present invention, there is provided an implantable piezoelectric / conductive double-layer composite membrane, wherein the implantable piezoelectric / conductive double-layer composite membrane is composed of a composite conductive biomaterial layer and a piezoelectric layer, wherein the piezoelectric layer is bonded and covered on the composite conductive biomaterial layer, wherein the composite conductive biomaterial layer is composed of chitosan and chitosan-grafted reduced graphene oxide, and the piezoelectric layer is composed of piezoelectric fibers.

[0068] Specifically, the composite conductive biomaterial layer includes a chitosan layer as a main support structure, and the chitosan-grafted reduced graphene oxide is continuously dispersed in the chitosan layer to form a continuous path for conduction. At the same time, the reduced graphene oxide continuously dispersed in the chitosan layer makes the surface of the composite conductive biomaterial layer have a certain degree of roughness.

[0069] Specifically, the piezoelectric fiber contains poly-L-lactic acid as a main component. Poly-L-lactic acid in a filamentous state has excellent piezoelectric properties.

[0070] According to another embodiment, a method for preparing an implantable piezoelectric / conductive double-layer composite film is provided, wherein the implantable piezoelectric / conductive double-layer composite film is the implantable piezoelectric / conductive double-layer composite film described above, and the preparation method comprises:

[0071] S100 prepared chitosan-grafted reduced graphene oxide;

[0072] S200 prepares a mixed solution containing a chitosan solution and the chitosan-grafted reduced graphene oxide;

[0073] S300: applying the mixed solution onto a support member and air-drying the mixed solution, and then washing and drying the mixed solution to obtain a composite conductive biomaterial layer;

[0074] S400: spinning a piezoelectric layer composed of piezoelectric fibers on the composite conductive biomaterial layer to obtain a piezoelectric / conductive double-layer composite film.

[0075] Specifically, the preparation of chitosan-grafted reduced graphene oxide by S100 comprises the following steps:

[0076] S110 dissolving chitosan powder with a molecular weight of 200 to 300 KDa in, for example, an acetic acid solution, stirring and standing at room temperature for 2 to 3 hours, removing residual bubbles, and obtaining a first chitosan solution;

[0077] S120 placing graphene oxide powder in deionized water and ultrasonically obtaining a graphene oxide dispersion;

[0078] S130: adding the graphene oxide dispersion dropwise to the first chitosan solution, stirring at room temperature and ultrasonicating to obtain a mixed solution containing chitosan and graphene oxide; in the mixed solution, the mass ratio of chitosan to graphene oxide is preferably (5-10):1, and this ratio enables the reduced graphene oxide to be fully grafted with chitosan during the subsequent reduction reaction.

[0079] S140: The mixed solution containing chitosan and graphene oxide is heated to 80-100° C. for reduction reaction. After the reaction is completed, centrifugation is performed to obtain a precipitate. The precipitate is washed (for example, the precipitate is washed with 1% acetic acid and deionized water in sequence, 5 times, each time for 30 minutes) and then freeze-dried (for example, the freezing temperature is -20° C., the freezing time is 3 hours, and the freeze-drying time is 48 hours) to obtain a powdered chitosan-grafted reduced graphene oxide.

[0080] S200 prepares a mixed solution containing a chitosan solution and the chitosan-grafted reduced graphene oxide, specifically comprising the following steps:

[0081] S210 prepares a second chitosan solution;

[0082] S220: adding the powdered chitosan-grafted reduced graphene oxide into the second chitosan solution, stirring evenly, to obtain a mixed solution containing the chitosan solution and the chitosan-grafted reduced graphene oxide.

[0083] Preferably, in the mixed solution, the mass ratio of chitosan to the chitosan-grafted reduced graphene oxide is (4-7): 1. The mixed solution of this ratio can form a film, can avoid the cytotoxicity caused by excessive reduced graphene oxide, and importantly, has good mechanical properties while meeting the requirements of electrical conductivity.

[0084] S300: applying the mixed solution to the support member and air drying it, and then washing and drying it to obtain the composite conductive biomaterial layer, specifically comprising the following steps:

[0085] S310: Evenly spread the mixed solution on an adhesive glass slide, then place it on a horizontal surface and let it stand until all bubbles are removed. Then, keep it horizontal and place it in a clean fume hood to air dry to obtain a membrane.

[0086] S320: washing the obtained membrane with 10% NaOH solution and deionized water in turn to remove residual acetic acid;

[0087] S330 puts the cleaned membrane into an ultra-clean fume hood and air-dries it, and the obtained membrane is the composite conductive biomaterial layer.

[0088] S400 forms a piezoelectric layer composed of piezoelectric fibers on the composite conductive biomaterial layer to obtain a piezoelectric / conductive double-layer composite film, which specifically includes the following steps:

[0089] S410 dissolves poly-L-lactic acid in a solvent and stirs to obtain a spinning solution; the solvent is preferably a mixed solvent of dichloromethane and N,N-dimethylformamide. The mixed solvent can improve the crystallinity of poly-L-lactic acid and increase its piezoelectricity, and when the weight ratio of poly-L-lactic acid, dichloromethane and N,N-dimethylformamide is 0.25:2.85:1.9, the piezoelectricity of poly-L-lactic acid reaches the best.

[0090] S420 uses electrospinning to spin the spinning solution in the form of fibers on the composite conductive biomaterial layer to form a piezoelectric layer composed of piezoelectric fibers.

[0091] Preferably, the electrospinning process is specifically as follows: fixing the composite conductive biomaterial layer on a drum collector, transferring the spinning solution to a syringe equipped with an electrospinning machine, setting spinning parameters, and spinning the spinning solution in the form of fibers on the composite conductive biomaterial layer.

[0092] The spinning parameters preferably adopt the following parameters:

[0093] The flow rate of the spinning solution was set at 2 mL / h at 30°C and 55% relative humidity. A high voltage of 20 kV was applied between the needle and the collector, and the distance was 200 mm. The fibers were collected using a rotating drum collector at a rotation speed of 1350 rpm.

[0094] According to another embodiment, an implantable piezoelectric / conductive double-layer composite stent is provided, wherein the implantable piezoelectric / conductive double-layer composite stent is made of the above-mentioned implantable piezoelectric / conductive double-layer composite film or the implantable piezoelectric / conductive double-layer composite film prepared by the preparation method.

[0095] In one embodiment of the present invention, the implantable piezoelectric / conductive double-layer composite stent is a double-layer structure with a through lumen, the piezoelectric layer is the outer layer of the double-layer structure, and the composite conductive biomaterial layer is the inner layer of the double-layer structure.

[0096] In another embodiment of the present invention, a method for preparing an implantable piezoelectric / conductive double-layer composite stent is provided, the preparation method comprising the following steps:

[0097] The implantable piezoelectric / conductive bilayer composite film is wound on a support rod, such as a stainless steel round rod;

[0098] Coating the side joints with methacrylated gelatin;

[0099] The methacryloyl gelatin is solidified by ultraviolet irradiation to form a double-layer composite stent with a through lumen.

[0100] The amino substitution degree of the methacryloyl gelatin is 30-90±5%, the molecular weight is 100-200KDa, and the concentration is 5-10%.

[0101] According to one embodiment of the present invention, there is provided an implantable piezoelectric / conductive double-layer composite film, an implantable piezoelectric / conductive double-layer composite stent, and the use of the piezoelectric / conductive double-layer composite stent prepared by the above-mentioned preparation method in the preparation of an implantable piezoelectric / conductive double-layer composite stent for repairing nerve damage.

[0102] The chitosan used in the embodiment of the present invention is chitosan powder with a molecular weight of 200 to 300 KDa.

[0103] Example 1

[0104] A method for preparing an implantable piezoelectric / conductive double-layer composite film comprises the following steps:

[0105] (1) Add 5 g of chitosan and 5 g of acetic acid into 390 ml of deionized water to dissolve, stir at room temperature for 24 h, let stand for 2 to 3 h, remove residual bubbles, and obtain a chitosan solution;

[0106] (2) adding 1 g of graphene oxide to 99 ml of deionized water, dispersing and ultrasonicating for two hours to obtain a graphene oxide dispersion;

[0107] (3) adding the graphene oxide dispersion obtained in step (2) dropwise into the chitosan solution in step (1), stirring at room temperature for 12 h and ultrasonicating for 3 h to obtain a first mixed solution containing both chitosan and chitosan-grafted graphene oxide.

[0108] (4) stirring the first mixed solution at 90° C. for 6 h, and then centrifuging at 12,000 rpm for 30 min to collect the precipitate;

[0109] The precipitate was washed with 1% acetic acid and deionized water in turn for 5 times, each time for 30 minutes, with the volume of acetic acid solution and deionized water used each time being 500 ml, the freezing temperature being -20°C, the freezing time being 3 hours, and the freeze dryer drying time being 48 hours to obtain chitosan-grafted reduced graphene oxide powder.

[0110] (5) Add 0.7 g of chitosan and 0.4 g of acetic acid into 18.8 ml of deionized water to dissolve, stir at room temperature for 24 h, let stand for 2 to 3 h, remove residual bubbles, and obtain another chitosan solution;

[0111] 0.1 g of the chitosan-grafted reduced graphene oxide powder obtained in step (4) was added to the other chitosan solution and stirred to obtain a second mixed solution.

[0112] (6) 1.5 ml of the second mixed solution obtained in step (5) is evenly coated on a 2 cm × 4 cm adhesive slide. The slide has been hydrophilized at 500°C in a muffle furnace and rinsed and dried. The slide coated with the solution is first placed on a horizontal surface and allowed to stand for 30 minutes. After completely removing bubbles, it is kept horizontal and placed in an ultra-clean fume hood. The lowest wind speed is set to level 1 and air-dried for 8 hours to obtain a film.

[0113] (7) Soak the completely air-dried membrane in step (6) in a 10% NaOH solution for 1 hour to remove residual acetic acid.

[0114] (8) Soak the membrane in step (7) in deionized water, replacing the deionized water every 30 minutes for the first four times and every 60 minutes for the next four times to remove residual NaOH and acetic acid, so that the pH of the soaking solution is ultimately the same as that of the deionized water.

[0115] (9) Place the membrane in step (8) in a clean fume hood, set the lowest wind speed to level 1, and air dry for 8 hours. After the membrane A is dried, fix it on the electrospinning drum using double-sided tape.

[0116] (10) 0.25 g of poly-L-lactic acid was added to a mixed solution of 2.85 g of dichloromethane and 1.9 g of N,N-dimethylformamide to dissolve to obtain a poly-L-lactic acid solution; the solution was transferred to a 5 ml plastic syringe equipped with a 20-gauge needle, and the flow rate of the poly-L-lactic acid solution was set to 2 mL / h at 30°C and 55% relative humidity. A high voltage of 20 kV was applied between the needle and a rotating drum collector at a distance of 200 mm. The fibers were collected using a rotating drum collector at a rotation speed of 1350 rpm to obtain an implantable piezoelectric / conductive double-layer composite film.

[0117] Furthermore, the implantable piezoelectric / conductive double-layer composite stent can be prepared based on the aforementioned steps (1)-(10).

[0118] (11) The implantable piezoelectric / conductive double-layer composite film in step (10) was wrapped around a stainless steel round rod, and methacrylated gelatin was coated on the side connection. It was cured by ultraviolet irradiation (405 nm, 25 mW / cm2, irradiation for 1 min) to form a double-layer composite stent with a through lumen, named CGP0.5.

[0119] The amino substitution degree of the methacrylated gelatin is 30-90±5%, the molecular weight is 100-200KDa, and the concentration is 5-10%. The inner layer of the double-layer composite stent with a through lumen is a mixture of chitosan and chitosan-grafted reduced graphene oxide, and the outer layer is composed of poly-L-lactic acid fiber to form an implantable piezoelectric / conductive double-layer composite capacitor stent.

[0120] (12) The implantable piezoelectric / conductive double-layer composite capacitor stent in step (11) is photographed by scanning electron microscopy (SEM) Figure 1 The Young's modulus was measured by a universal testing machine and was 19.10±0.7546MPa (as shown in Figure 2 As shown in the figure, the conductivity is (4.476±0.529)×10 -2 S / m (such as Figure 3 shown).

[0121] Example 2

[0122] A method for preparing an implantable piezoelectric / conductive double-layer composite film comprises the following steps:

[0123] (1) Add 5 g of chitosan and 5 g of acetic acid to 390 ml of deionized water to dissolve, stir at room temperature for 24 h, let stand for 2 to 3 h, remove residual bubbles, and obtain a chitosan solution; add 1 g of graphene oxide to 99 ml of deionized water, disperse and ultrasonicate for two hours to obtain a graphene oxide dispersion.

[0124] (2) adding the graphene oxide dispersion obtained in step (1) dropwise into the chitosan solution, stirring at room temperature for 12 h and ultrasonicating for 3 h to obtain a first mixed solution containing both chitosan and chitosan-grafted graphene oxide.

[0125] (3) The first mixed solution obtained in step (2) is stirred and reacted at 90° C. for 6 hours to obtain a first mixed solution containing both chitosan and chitosan-grafted reduced graphene oxide.

[0126] (4) The first mixed solution obtained in step (3) is centrifuged at 12000 rpm for 30 min to collect the precipitate, and the precipitate is washed with 1% acetic acid and deionized water in turn, for 5 times, each time for 30 min, with the volume of acetic acid solution and deionized water used each time being 500 ml, the freezing temperature being -20°C, the freezing time being 3 h, and the freeze dryer drying time being 48 h to obtain chitosan-grafted reduced graphene oxide powder.

[0127] (5) Add 0.6 g of chitosan and 0.4 g of acetic acid into 18.8 ml of deionized water to dissolve, stir at room temperature for 24 h, let stand for 2 to 3 h, remove residual bubbles, and obtain a chitosan solution. Add 0.2 g of the chitosan-grafted reduced graphene oxide powder obtained in step (4) into the chitosan solution and stir to mix.

[0128] (6) 1.5 ml of the solution obtained in step (5) was evenly coated on a 2 cm × 4 cm adhesive glass slide. The glass slide had been hydrophilized at 500°C in a muffle furnace and rinsed and dried. The glass slide coated with the solution was placed on a horizontal surface and allowed to stand for 30 minutes. After completely removing the bubbles, it was kept horizontal and placed in an ultra-clean fume hood. The lowest wind speed was set to level 1 and air-dried for 8 hours.

[0129] (7) Soak the completely air-dried membrane in step (6) in a 10% NaOH solution for 1 hour to remove residual acetic acid.

[0130] (8) Soak the membrane in step (7) in deionized water, replacing the deionized water every 30 minutes for the first four times and every 60 minutes for the next four times to remove residual NaOH and acetic acid, so that the pH of the soaking solution is ultimately the same as that of the deionized water.

[0131] (9) Place the membrane in step (8) in a clean fume hood, set the lowest wind speed to level 1, and air-dry for 8 h. After the membrane is dried, fix it on the electrospinning drum using double-sided tape.

[0132] (10) 0.25 g of poly-L-lactic acid was added to a mixed solution of 2.85 g of dichloromethane and 1.9 g of N,N-dimethylformamide to dissolve the mixture, thereby obtaining a poly-L-lactic acid solution.

[0133] The solution was transferred to a 5 ml plastic syringe equipped with a 20-gauge needle. The flow rate of the poly-L-lactic acid solution was set to 2 mL / h at 30 °C and 55% relative humidity. A high voltage of 20 kV was applied between the needle and the collector at a distance of 200 mm. A rotating drum collector was used to collect the fibers at a rotation speed of 1350 rpm to obtain an implantable piezoelectric / conductive double-layer composite film.

[0134] Furthermore, the implantable piezoelectric / conductive double-layer composite stent can be prepared based on the aforementioned steps (1)-(10).

[0135] (11) The implantable piezoelectric / conductive double-layer composite film in step (10) is wound on a stainless steel round rod, and methacrylated gelatin is coated on the side opening, and cured by ultraviolet irradiation (405nm, 25mW / cm2, irradiation for 1min) to form a double-layer composite stent with a through lumen, named CGP1. The amino substitution degree of the methacrylated gelatin is 30-90±5%, the molecular weight is 100-200KDa, and the concentration is 5-10%. The inner layer of the double-layer composite stent with a through lumen is a mixture of chitosan and chitosan-grafted reduced graphene oxide, and the outer layer is composed of poly-L-lactic acid fiber.

[0136] (12) The piezoelectric / conductive double-layer composite capacitor support in step (11) is photographed by scanning electron microscopy (SEM) Figure 1 The Young's modulus was measured by a universal testing machine and was 20.06±1.854MPa (as shown in Figure 2 As shown in the figure, the conductivity is (4.962±0.487)×10 -2 S / m (such as Figure 3 shown).

[0137] Example 3

[0138] A method for preparing an implantable piezoelectric / conductive double-layer composite film comprises the following steps:

[0139] (1) Add 5 g of chitosan and 5 g of acetic acid into 390 ml of deionized water to dissolve, stir at room temperature for 24 h, let stand for 2 to 3 h, remove residual bubbles, and obtain a chitosan solution;

[0140] 1 g of graphene oxide was added to 99 ml of deionized water for dispersion and ultrasonication for two hours to obtain a graphene oxide dispersion.

[0141] (2) adding the graphene oxide dispersion obtained in step (1) dropwise into the chitosan solution, stirring at room temperature for 12 h and ultrasonicating for 3 h to obtain a graphene oxide mixed solution containing both chitosan and chitosan grafted thereto.

[0142] (3) The mixed solution obtained in step (2) was stirred and reacted at 90° C. for 6 hours to obtain a mixed solution containing chitosan and chitosan-grafted reduced graphene oxide.

[0143] (4) centrifuging the mixed solution obtained in step (3) at 12000 rpm for 30 min to collect the precipitate; washing the precipitate with 1% acetic acid and deionized water, respectively, for 5 times, each time for 30 min, with the volume of acetic acid solution and deionized water used each time being 500 ml, the freezing temperature being -20°C, the freezing time being 3 h, and the freeze dryer drying time being 48 h, to obtain chitosan-grafted reduced graphene oxide powder.

[0144] (5) Add 0.5 g of chitosan and 0.4 g of acetic acid into 18.8 ml of deionized water to dissolve, stir at room temperature for 24 h, let stand for 2-3 h, remove residual bubbles, and obtain another chitosan solution; 0.3 g of the chitosan-grafted reduced graphene oxide powder obtained in step (4) is added to the another chitosan solution and stirred to mix.

[0145] (6) 1.5 ml of the solution obtained in step (5) was evenly coated on a 2 cm × 4 cm adhesive glass slide. The glass slide had been hydrophilized at 500°C in a muffle furnace and rinsed and dried. The glass slide coated with the solution was placed on a horizontal surface and allowed to stand for 30 minutes. After completely removing the bubbles, it was kept horizontal and placed in an ultra-clean fume hood. The lowest wind speed was set to level 1 and air-dried for 8 hours.

[0146] (7) Soak the completely air-dried membrane in step (6) in a 10% NaOH solution for 1 hour to remove residual acetic acid.

[0147] (8) Soak the membrane in step (7) in deionized water, replacing the deionized water every 30 minutes for the first four times and every 60 minutes for the next four times to remove residual NaOH and acetic acid, so that the pH of the soaking solution is ultimately the same as that of the deionized water.

[0148] (9) Place the membrane in step (8) in a clean fume hood, set the lowest wind speed to level 1, and air-dry for 8 h. After the membrane is dried, fix it on the electrospinning drum using double-sided tape.

[0149] (10) 0.25 g of poly-L-lactic acid was added to a mixed solution of 2.85 g of dichloromethane and 1.9 g of N,N-dimethylformamide to dissolve, thereby obtaining a poly-L-lactic acid solution; the solution was transferred to a 5 ml plastic syringe equipped with a 20-gauge needle, and the flow rate of the poly-L-lactic acid solution was set to 2 mL / h at 30 °C and 55% relative humidity. A high voltage of 20 kV was applied between the needle and the collector, and the distance was 200 mm. The fibers were collected using a rotating drum collector at a rotation speed of 1350 rpm to obtain a piezoelectric / conductive double-layer composite film.

[0150] Furthermore, the implantable piezoelectric / conductive double-layer composite stent can be prepared based on the aforementioned steps (1)-(10).

[0151] (11) Wrap the piezoelectric / conductive double-layer composite film in step (10) on a stainless steel round rod, coat the side opening with methacrylic gelatin, and cure it by ultraviolet irradiation (405nm, 25mW / cm2, irradiation for 1min) to form a double-layer composite stent with a through lumen, named CGP1.5. The methacrylic gelatin has an amino substitution degree of 30-90±5%, a molecular weight of 100-200KDa, and a concentration of 5-10%. The inner layer of the double-layer composite stent with a through lumen is a mixture of chitosan and chitosan-grafted reduced graphene oxide, and the outer layer is composed of poly-L-lactic acid fiber.

[0152] (12) The piezoelectric / conductive double-layer composite capacitor support in step (11) is photographed by scanning electron microscopy (SEM) Figure 1 The Young's modulus was measured by a universal testing machine and was 24.09±2.082MPa (as shown in Figure 2 As shown), the conductivity is (5.381±0.518)×10-2S / m (as shown) through the four-probe conductivity meter test. Figure 3 shown).

[0153] Example 4

[0154] A method for preparing an implantable piezoelectric / conductive double-layer composite film comprises the following steps:

[0155] (1) Add 5 g of chitosan and 5 g of acetic acid to 390 ml of deionized water to dissolve, stir at room temperature for 24 h, let stand for 2-3 h, remove residual bubbles, and obtain a chitosan solution. Add 1 g of graphene oxide to 99 ml of deionized water, disperse and sonicate for two hours to obtain a graphene oxide dispersion.

[0156] (2) adding the graphene oxide dispersion obtained in step (1) dropwise into the chitosan solution, stirring at room temperature for 12 h and ultrasonicating for 3 h to obtain a mixed solution containing both chitosan and chitosan-grafted graphene oxide.

[0157] (3) The mixed solution obtained in step (2) was stirred and reacted at 90° C. for 6 hours to obtain a mixed solution containing chitosan and chitosan-grafted reduced graphene oxide.

[0158] (4) The mixed solution obtained in step (3) was centrifuged at 12000 rpm for 30 min to collect the precipitate. The precipitate was washed with 1% acetic acid and deionized water in turn for 5 times, each time for 30 min, the volume of acetic acid solution and deionized water used each time was 500 ml, the freezing temperature was -20°C, the freezing time was 3 h, and the freeze dryer drying time was 48 h to obtain chitosan-grafted reduced graphene oxide powder.

[0159] (5) Add 0.4 g of chitosan and 0.4 g of acetic acid into 18.8 ml of deionized water to dissolve, stir at room temperature for 24 h, let stand for 2-3 h, remove residual bubbles, and obtain another chitosan solution. Add 0.4 g of the chitosan-grafted reduced graphene oxide powder obtained in step (4) to the another chitosan solution and stir to mix.

[0160] (6) 1.5 ml of the solution obtained in step (5) was evenly coated on a 2 cm × 4 cm adhesive glass slide. The glass slide had been hydrophilized at 500°C in a muffle furnace and rinsed and dried. The glass slide coated with the solution was placed on a horizontal surface and allowed to stand for 30 minutes. After completely removing the bubbles, it was kept horizontal and placed in an ultra-clean fume hood. The lowest wind speed was set to level 1 and air-dried for 8 hours.

[0161] (7) Soak the completely air-dried membrane in step (6) in a 10% NaOH solution for 1 hour to remove residual acetic acid.

[0162] (8) Soak the membrane in step (7) in deionized water, replacing the deionized water every 30 minutes for the first four times and every 60 minutes for the next four times to remove residual NaOH and acetic acid, so that the pH of the soaking solution is ultimately the same as that of the deionized water.

[0163] (9) Place the membrane in step (8) in a clean fume hood, set the lowest wind speed to level 1, and air-dry for 8 h. After the membrane is dried, fix it on the electrospinning drum using double-sided tape.

[0164] (10) 0.25 g of poly-L-lactic acid was dissolved in a mixed solution of 2.85 g of dichloromethane and 1.9 g of N,N-dimethylformamide to obtain a poly-L-lactic acid solution. The solution was transferred to a 5 ml plastic syringe equipped with a 20-gauge needle. The flow rate of the poly-L-lactic acid solution was set to 2 mL / h at 30 °C and 55% relative humidity. A high voltage of 20 kV was applied between the needle and the collector, and the distance was 200 mm. The fibers were collected using a rotating drum collector at a rotation speed of 1350 rpm to obtain an implantable piezoelectric / conductive double-layer composite film.

[0165] Furthermore, the implantable piezoelectric / conductive double-layer composite stent can be prepared based on the aforementioned steps (1)-(10).

[0166] (11) The piezoelectric / conductive double-layer composite film in step (10) is wound on a stainless steel round rod, and methacrylated gelatin is coated on the side opening, and cured by ultraviolet irradiation (405nm, 25mW / cm2, irradiation for 1min) to form a double-layer composite stent with a through lumen, named CGP2. The methacrylated gelatin has an amino substitution degree of 30-90±5%, a molecular weight of 100-200KDa, and a concentration of 5-10%. The inner layer of the double-layer composite stent with a through lumen is a mixture of chitosan and chitosan-grafted reduced graphene oxide, and the outer layer is composed of poly-L-lactic acid fiber.

[0167] (12) The acetic acid piezoelectric / conductive double-layer composite capacitor support in step (11) is photographed by scanning electron microscopy (SEM) Figure 1 The Young's modulus was measured by a universal testing machine and was 24.82±2.971MPa (as shown in Figure 2 As shown in the figure, the conductivity is (5.8±0.642)×10 -2 S / m (such as Figure 3 shown).

[0168] Example 5 Preparation of CGP2.5

[0169] Step (5) in Example 1 is modified as follows: 0.3 g of chitosan and 0.4 g of acetic acid are added to 18.8 ml of deionized water to dissolve, stirred at room temperature for 24 h, allowed to stand for 2 to 3 h, residual bubbles are removed, 0.5 g of chitosan-grafted reduced graphene oxide powder is added, stirred and mixed, and a second mixed solution is obtained.

[0170] The prepared double-layer composite stent with a through lumen was named CGP2.5

[0171] The microscopic morphology SEM images were taken by scanning electron microscope (such as Figure 1 The Young's modulus of CGP2.5 measured by a universal testing machine is: 9.534±2.889MPa (as shown in Figure 2 As shown), the conductivity is 0.0623±0.00637S / m as tested by a four-probe conductivity meter. Figure 3 shown).

[0172] Comparative Example 1

[0173] (1) 1 g of graphene oxide was added to 99 ml of deionized water, dispersed and ultrasonicated for two hours to obtain a graphene oxide dispersion.

[0174] (2) The solution obtained in step (1) was stirred and reacted at 90° C. for 6 h to obtain a reduced graphene oxide dispersion.

[0175] (3) The solution obtained in step (2) was centrifuged at 12000 rpm for 30 min to collect the precipitate, and freeze-dried at a freezing temperature of -20°C for 3 h and a freeze dryer drying time of 48 h to obtain reduced graphene oxide powder.

[0176] (4) 0.25 g of poly-L-lactic acid was added to a mixed solution of 2.835 g of dichloromethane and 1.89 g of N,N-dimethylformamide to dissolve to obtain a poly-L-lactic acid solution, and 0.025 g of the reduced graphene oxide powder in step (3) was added to obtain a mixed suspension.

[0177] (5) The mixed solution in step (4) was transferred into a 5 ml plastic syringe equipped with a 20-gauge needle. The flow rate of the solution was set to 2 mL / h at 30°C and 55% relative humidity. A high voltage of 20 kV was applied between the needle and the collector at a distance of 200 mm. The fibers were collected using a collector at a rotation speed of 1350 rpm to obtain a poly-L-lactic acid fiber conduit doped with reduced graphene oxide.

[0178] (6) The fiber conduit in step (5) was tested by a universal testing machine to obtain a Young's modulus of 17.33±1.104 MPa ( Figure 2 As shown), the conductivity is (4.04±0.486)×10-2S / m (as shown) through the four-probe conductivity meter test. Figure 3 shown).

[0179] In terms of mechanical properties, according to Figure 2 , 3 It can be seen that the mechanical properties of the samples obtained in Examples 1-4 of the present invention are better than those of the samples obtained in Comparative Example 1, because after the reduced graphene oxide is grafted with chitosan, an amide bond is formed between them, and after mixing it with chitosan, it is equivalent to having an amide bond as a connection method compared with the pure chitosan film, which is relatively more solid. In Examples 1-4, as the amount of reduced graphene oxide grafted with chitosan increases, the mechanical properties are better, and the reason is also due to the presence of amide bonds. Specifically, although the amount of chitosan used decreases, the reduced graphene oxide grafted with chitosan increases. On the one hand, the chitosan grafted thereon replaces the reduced chitosan, and on the other hand, due to the presence of amide bonds, the mechanical properties are slightly increased. However, the mechanical properties of the sample in Example 5 are significantly reduced, because the chitosan solution has a good dispersing effect on the reduced graphene oxide grafted with chitosan. If a lot of reduced graphene oxide grafted with chitosan is added, and chitosan is very little, then rGO will aggregate, so the mechanical properties of CGP2.5 deteriorate.

[0180] In terms of electrical conductivity, Figure 2 , 3It can be seen that the conductivity of the samples obtained in Examples 1-4 of the present invention is better than that of the sample obtained in Comparative Example 1. Analyzing the reason, on the one hand, after chitosan is grafted with reduced graphene oxide in the embodiments of the present application, rGO can be dispersed in the entire layer, and in the final film, rGO is evenly distributed, and a continuous path can be formed for conduction. In the preparation method of Comparative Example 1, because rGO is not grafted or bonded with PLLA, and is not soluble in the solvent, it cannot be evenly distributed by dispersion alone. Therefore, rGO is easy to agglomerate and will not form a uniformly dispersed suspension state, resulting in less and uneven rGO on the surface of PLLA in the final sample, so the transmission efficiency of the piezoelectric charge generated by PLLA becomes low. In Examples 1-4, as the content of reduced graphene oxide grafted with chitosan increases, the conductivity of the material gradually increases.

[0181] Test Example 1 Determination of the electrical signal output of the piezoelectric / conductive double-layer composite film

[0182] (1) The piezoelectric / conductive double-layer composite films of Example 2 and Comparative Example 1 were cut into squares of 1 cm×1 cm respectively.

[0183] (2) Cover each side of the composite film in step (1) with aluminum foil of the same size, and adhere the composite film and the aluminum foil together with a conductive adhesive. Copper wires are led out from the aluminum foil on both sides for external connection.

[0184] (3) Encapsulating the entire material in step (2) in a polyimide film.

[0185] (4) The material in step (3) was measured using an electrochemical workstation (Chi 760e). The results showed that the implantable piezoelectric / conductive double-layer composite film in Example 2 had a stable current (e.g. Figure 4 a) and voltage (as Figure 4 b) output, which is higher than the current of the fiber conduit in Comparative Example 1 (as shown in Figure 4 c) and voltage (as Figure 4 d) output.

[0186] Test Example 2 Determination of blood compatibility of piezoelectric / conductive double-layer composite film

[0187] (1) Collect 2 mL of rabbit blood using a blue-cap anticoagulant tube (BD, 9NC Coagulation sodium citrate 3.8%), take 1 mL of healthy fresh anticoagulated rabbit blood, and dilute it with 1.25 mL of 0.9% saline to prepare diluted anticoagulated rabbit blood.

[0188] (2) Take 0.025 g of each of the piezoelectric / conductive double-layer composite films of Examples 1, 2, 3 and 4 and the composite film of Comparative Example 1 and add them into 15 ml centrifuge tubes containing 5 ml of normal saline (4 parallel samples are set up in each group). Only 5 ml of distilled water is added to each tube of the positive control group, and only 5 ml of normal saline is added to each tube of the negative control group.

[0189] (3) Place all the centrifuge tubes in step (2) in a 37°C incubator and incubate for 30 minutes. After the incubation time is over, add 100 μL of the diluted anticoagulated rabbit blood preheated in step (1) to each tube and incubate in a 37°C incubator for 1 hour.

[0190] (4) Centrifuge at room temperature (3000 rpm, 5 min), and take 300 μL of the supernatant into a 96-well plate. Use an ELISA reader to detect the absorbance value A at a wavelength of 545 nm and calculate the hemolysis rate. Compared with the positive control group and the negative control group, the results showed that the implantable piezoelectric / conductive double-layer composite membrane has good blood compatibility (such as Figure 5 shown).

[0191] Test Example 3 Determination of Cytotoxicity of Piezoelectric / Conductive Composite Films by MTT Method

[0192] (1) The piezoelectric / conductive double-layer composite films of Examples 1, 2, 3 and 4 and the composite film of Comparative Example 1 were cut into pieces with an area of ​​3 cm 2 After UV sterilization for 24 h, the strips of different sizes were rinsed three times with sterile water and once with PBS, and placed in a 24-well plate for later use.

[0193] (2) Add 1 ml of L-DMEM basal medium or RPMI-1640 basal medium to each well of the well plate in step (1), and place the well plate soaked with the material in a 5% CO 2 , 37°C constant temperature cell culture incubator, static extraction for 24 hours. At the same time, mouse epithelial fibroblast cell line L929 cells were inoculated in a blank 96-well plate, 5000 cells per well.

[0194] (3) The extract in step (2) was transferred to a centrifuge tube, centrifuged at 1000 rpm / min for 5 min, and FBS and PS were added to prepare a complete medium for the extract, wherein the medium used for L929 cells was L-DMEM complete medium containing 10% FBS + 1% PS, and the cell wells of the blank control group were the above complete medium without the extract.

[0195] (4) Remove the old culture medium from the 96-well plate inoculated with L929 cells in step (3), rinse with PBS, add 100 ul of complete culture medium to each well, and place in a 5% CO 2 , 37℃ constant temperature cell culture incubator, culture for 48h.

[0196] (5) The cells cultured in step (4) to the corresponding time point were discarded from the complete culture medium, 100 ul of MTT (5 mg / ml) working solution was added to each well, and the cells were incubated in a light-proof 37°C constant temperature cell culture incubator for 4 h.

[0197] (6) Add 100 μl of formazan solution to each well in step (5), place the well plate in a light-proof constant temperature shaker at 37°C, 50 rpm / min, and dissolve for 4 hours.

[0198] (7) The well plate in step (6) was gently shaken to ensure that there were no bubbles in the wells, and the absorbance value at a wavelength of 570 nm was measured. The results were compared with the blank control group (cells cultured alone in the well plate without adding materials) and the comparative example 1. The piezoelectric / conductive double-layer composite films of Examples 1-4 and the composite film in Comparative Example 1 had no obvious cytotoxicity to the mouse epithelial fibroblast cell line L929 cells (such as Figure 6 shown).

[0199] The implantable piezoelectric / conductive double-layer composite film and stent, preparation method and application thereof according to the embodiments of the present invention have at least one of the following advantages or at least a part of at least one of the advantages:

[0200] (1) In the embodiment of the present invention, chitosan-grafted graphene oxide is subjected to reduction reaction to prepare chitosan-grafted reduced graphene oxide, and chitosan is then used to disperse the chitosan-grafted reduced graphene oxide, so that the reduced graphene oxide can be evenly dispersed in the reaction system. In the prepared composite conductive biomaterial layer, the reduced graphene oxide is evenly distributed in the chitosan layer. On the one hand, the obtained conductive film has uniform conductivity (rGO can form a continuous path for conduction) and excellent mechanical strength. At the same time, chitosan imparts excellent biocompatibility and can avoid cytotoxicity caused by excessive reduced graphene oxide. On the other hand, the reduced graphene oxide evenly distributed in the chitosan layer forms a rough surface of the composite conductive biomaterial layer, which is conducive to the close combination of the piezoelectric fibers formed by electrospinning and the composite conductive biomaterial layer, forming a double-layer membrane structure with an outer layer of PLLA piezoelectric layer and an inner layer of a conductive layer composed of chitosan and chitosan-grafted reduced graphene oxide. The charge generated by the piezoelectric layer is located on the surface of the piezoelectric layer, and then transmitted outward through the connected and fitted conductive layer, which can maximize the transmission of electrical signals, thereby better inducing the growth of the two broken end nerves toward the middle, and preventing the downstream target muscles / organs from atrophying due to long-term loss of electrical stimulation;

[0201] (2) The natural polymer chitosan serves as the main support structure of the stent, providing good mechanical support for the entire catheter. The chitosan-grafted reduced graphene oxide continuously dispersed in the chitosan layer acts as a conductive medium. Poly-L-lactic acid serves as a piezoelectric layer, providing electrical signal output for the entire composite stent, which together give the catheter piezoelectric and conductive properties.

[0202] (3) Graphene oxide is grafted with chitosan through an amide reaction, and the graphene oxide is reduced to reduced graphene oxide, thereby further improving the dispersibility, conductivity and biocompatibility of the reduced graphene oxide in the chitosan solution;

[0203] (4) The present invention directly covers the poly-L-lactic acid fiber layer produced by electrospinning on the conductive layer, which can transmit the generated electrical signal to the conductive layer to the greatest extent; at the same time, the piezoelectric / conductive double-layer composite stent is an implantable stent, and its piezoelectric layer in the body can directly receive muscle pressure stimulation, thereby quickly and effectively generating an electrical signal response;

[0204] (5) The substrates selected in the present invention are all green and harmless materials that are biodegradable and biocompatible. They are completed in a neutral environment through acid-base neutralization, which simplifies the production process and greatly avoids the adverse effects caused by toxic organic solvents remaining in in vitro cell culture and scaffold implantation in vivo;

[0205] (6) The implantable piezoelectric / conductive double-layer composite stent of the present invention has better mechanical support, better conductivity, better electrical signal output capability, better antibacterial effect, provides a favorable microenvironment for cell adhesion, proliferation and differentiation, has a better promoting effect on peripheral nerve regeneration and repair, and can be more widely applicable to different types of peripheral nerve injury repair;

[0206] (7) The piezoelectric layer is covered on the surface of the conductive layer by electrospinning, and then curled into a double-layer piezoelectric / conductive stent with a through-hole in the middle. The formed stent has good conductivity, electrical signal output performance, mechanical properties and biosafety, and can provide good physical support and regenerative microenvironment for the repair of peripheral nerve injury.

[0207] Although some embodiments of the present general inventive concept have been shown and described, it will be appreciated by those skilled in the art that changes may be made to these embodiments without departing from the principles and spirit of the present general inventive concept, the scope of which is defined by the claims and their equivalents.

Claims

1. An implantable piezoelectric / conductive double-layer composite film, characterized in that: The implantable piezoelectric / conductive double-layer composite film is composed of a composite conductive biomaterial layer and a piezoelectric layer, wherein the piezoelectric layer is laminated and covered on the composite conductive biomaterial layer, the composite conductive biomaterial layer is composed of chitosan and chitosan-grafted reduced graphene oxide, and the piezoelectric layer is composed of piezoelectric fibers.

2. The implantable piezoelectric / conductive double-layer composite film according to claim 1, characterized in that: The composite conductive biomaterial layer comprises a chitosan layer as a main supporting structure, and the chitosan-grafted reduced graphene oxide is dispersed in the chitosan layer.

3. The implantable piezoelectric / conductive double-layer composite film according to claim 1, characterized in that: The piezoelectric fibers contain poly-L-lactic acid as a main component.

4. A method for preparing an implantable piezoelectric / conductive double-layer composite film, wherein the implantable piezoelectric / conductive double-layer composite film is the implantable piezoelectric / conductive double-layer composite film according to any one of claims 1 to 3, and the preparation method comprises: S1 preparation of chitosan-grafted reduced graphene oxide; S2 preparing a mixed solution containing a chitosan solution and the chitosan-grafted reduced graphene oxide; S3: applying the mixed solution onto a support member and air-drying the mixed solution, and then washing and drying the mixed solution to obtain a composite conductive biomaterial layer; S4: spinning a piezoelectric layer composed of piezoelectric fibers on the composite conductive biomaterial layer to obtain a piezoelectric / conductive double-layer composite film.

5. The preparation method according to claim 4, characterized in that: The S1 step includes: A mixed solution containing chitosan and graphene oxide is prepared, a reduction reaction is carried out at 80-100° C., a precipitate is obtained by centrifugation, and the precipitate is washed and freeze-dried to obtain powdered chitosan-grafted reduced graphene oxide.

6. The preparation method according to claim 5, characterized in that: In the mixed solution containing chitosan and graphene oxide, the mass ratio of chitosan to graphene oxide is (5-10):

1.

7. The preparation method according to claim 4, characterized in that: In the mixed solution containing chitosan and the chitosan-grafted reduced graphene oxide, the mass of chitosan is greater than the mass of the chitosan-grafted reduced graphene oxide.

8. The preparation method according to any one of claims 3 to 7, characterized in that: The S4 step includes: Dissolving poly-L-lactic acid in a solvent to prepare a spinning solution; The spinning solution is covered on the composite conductive biomaterial layer in the form of fibers by electrostatic spinning to form a piezoelectric layer.

9. The preparation method according to claim 8, characterized in that: The solvent is obtained by mixing dichloromethane and N,N-dimethylformamide.

10. An implantable piezoelectric / conductive double-layer composite stent, wherein the implantable piezoelectric / conductive double-layer composite stent is made of an implantable piezoelectric / conductive double-layer composite film prepared by the preparation method according to any one of claims 1 to 3 or any one of claims 4 to 9.

11. A method for preparing an implantable piezoelectric / conductive double-layer composite stent, the method comprising the following steps: Winding the implantable piezoelectric / conductive double-layer composite film prepared according to any one of claims 1 to 3 or the preparation method of any one of claims 4 to 9 on a support rod; Coating the side joints with methacrylated gelatin; The methacryloyl gelatin is solidified by ultraviolet irradiation to form a double-layer composite stent with a through lumen; The outer layer of the double-layer composite stent is a piezoelectric layer, and the inner layer is a composite conductive biomaterial layer.

12. The preparation method according to claim 11, characterized in that: The support rod comprises a stainless steel round bar; The amino substitution degree of the methacryloyl gelatin is 30-90±5%, the molecular weight is 100-200KDa, and the concentration is 5-10%.

13. An implantable piezoelectric / conductive double-layer composite film prepared by the preparation method according to any one of claims 1-3 or any one of claims 4-9, an implantable piezoelectric / conductive double-layer composite stent according to claim 10, and a piezoelectric / conductive double-layer composite stent prepared by the preparation method according to claim 11 or 12, in the preparation of an implantable piezoelectric / conductive double-layer composite stent for nerve damage repair.